How to build single‐celled cnidarians with worm‐like motility: Lessons from Myxozoa. Issue 3 (13th October 2021) - Adriano, Edson A.; Zatti, Suellen A.; Okamura, Beth
Abstract: Metazoans with worm‐like morphologies across diverse and disparate groups typically demonstrate motility generated by hydrostatic skeletons involving tissue layers (muscles and epithelia). Here we present representative morphological, behavioural and molecular data for parasitic cnidarians (myxozoans) that demonstrate unprecedented variation in form and function, developing as cellular hydrostats. Motile elongate plasmodia characterise a remarkable radiation of species in the genus Ceratomyxa . The vermiform plasmodia inhabit gall bladders of a range of South American freshwater fish and exhibit undulatory motility reminiscent of nematodes but achieved at the cellular level. Collective insights from ultrastructure, confocal and light microscopy along with videos depicting movements highlight key features that we propose explain the unique motility of the plasmodia. These features include cytoskeletal elements (net forming microfilaments and microtubules), a large internal vacuole, a relatively rigid outer glycocalyx and peripherally arranged mitochondria. These constituents provide collective evidence for repurposing of the cnidarian epitheliomuscular cell to support worm‐like motility at the cellular level. The apparent restriction of vermiform ceratomyxids to South American freshwaters suggests an origination via Cretaceous or Miocene marine transgressions and subsequent radiation. Abstract : Ultrastructure, confocal and light microscopy and videos were employed to understand how coordinated undulatory movement is achieved by an astonishing radiation of plasmodia‐forming vermiform endoparasites belonging to the genus Ceratomyxa (Cnidaria: Myxozoa: Myxosporea) that develop in gall bladders of South American freshwater fishes. Cytoskeletal elements (net forming microfilaments and microtubules), long tubular mitochondria, a large internal vacuole and a relatively rigid outer glycocalyx enable motility reminiscent of nematodes. The convergence in form to multicellular worms has involved repurposing of the fundamental cnidarian building block (epitheliomuscular cells) to form undulatory cellular hydrostats.